Target Strength of Juvenile Salmon, Oncorhynchus keta, for Acoustic Monitoring - MATSUURA, Tomohiko; FUKUDA, Yoshiaki; SAWADA, Kouichi (Kaiyou Onkyuo Gakkaishi, 2022)
It is well known that juvenile salmon tend to swim near the surface, and it is difficult to detect them using echo sounders whose beams are directed vertically downwards. Thus, an upwards looking transducer might be effective. In this case, it is vital to investigate the characteristics of ventral aspect target strength (TS). Here, we examined the relation of TS to length, as well as variations of average TS for juvenile salmon (Oncorhynchus keta). TS was predicted at four frequencies (38, 70, 120, and 200 kHz) using a prolate spheroid modal-series scattering model that described the swimbladder as a vacant prolate spheroid. The fish morphological parameters required for model calculations were obtained by digitizing soft X-ray images of fish. Model predictions were verified by TS measurements in a laboratory indoor tank. Averaged TS on different tilt-angle distribution was calculated. Normalized ventral TS by the squared standard length were predicted as -64.5 dB at 38 kHz, -65.2 dB at 70 kHz, -66.0 dB at 120 kHz, and -66.6 dB at 200 kHz, assuming normal tilt-angle distribution with a mean 0 deg and standard deviation of 20 deg. The variation of average TS decreased, and the average TS increased, with decreasing frequency. Among the four frequencies, it is advantageous to use 38 kHz for the acoustic survey of juvenile salmon due to high signal-to-noise ratio and insensitivity to the variation of tilt-angle distribution.